Endorsement as a Marketing Media Trend: A Case Study on By_aibee - Agus Wahyu Irawan; Wahyuni Wahyuni (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
Promotional activities through endorsements are currently being carried out more and more, but this makes the users and recipients of endorse services mostly not careful in doing endorsements on social media. Sometimes endorsements or celebgrams in promoting a product through social media are only based on perceptions, they are not in accordance with the reality, even the products being promoted are not used in real life in everyday life. They are also excessive in carrying out promotions related to endorsed products. If the celebgram ad includes using voice or verbal expressions, the bad impact is that people who don’t know experience fraud in advertising on Instagram just because the artist has a beautiful face and has many followers. The focus of celebgram is to introduce products in online media, both in the form of Instagram and other media. This research used a qualitative approach, with the type of field research. This research used interview observation method and in-depth documentation of the subject. The results of the research showed that to market products through Instagram were a form of consumer testimony for the products being marketed and then shown on Instagram so that potential buyers were interested in buying the product. The promotion of By_aibee products was carried out on Instagram accounts using an attractive appearance and not showing their bodies, and Accessivist choose Instagram celebrities who are beautiful, and have more attractiveness that was able to attract consumers to buy the promoted products. Prices matched the quality. The target for consumers was all people who needed products from By_aibee.